2012
DOI: 10.5489/cuaj.11038
|View full text |Cite
|
Sign up to set email alerts
|

Detrusor underactivity is prevalent after radical prostatectomy: a urodynamic study including risk factors

Abstract: Introduction: The objective was to determine the prevalence of, and factors that predict, detrusor underactivity (DU) in patients presenting with incontinence or lower urinary tract symptoms (LUTS) following radical prostatectomy (RP). We also determined the prevalence of bladder outlet obstruction (BOO) and detrusor overactivity (DO) in this population. Methods: Patients who underwent urodynamics post-RP were identified. Detrusor underactivity was defined as a maximum flow rate (Qmax) of ≤15 mL/s and detrusor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
0
18
2
Order By: Relevance
“…Another objective of this study was to evaluate the relative rates of DU in these 2 groups, as previous studies have shown a higher incidence of DU in patients who had undergone a minimally invasive procedure [11]. Contrary to the work by Chung et al, our data did not show increased rates of DU in patients following DVP compared to men who had undergone an open procedure.…”
Section: Methodscontrasting
confidence: 81%
See 3 more Smart Citations
“…Another objective of this study was to evaluate the relative rates of DU in these 2 groups, as previous studies have shown a higher incidence of DU in patients who had undergone a minimally invasive procedure [11]. Contrary to the work by Chung et al, our data did not show increased rates of DU in patients following DVP compared to men who had undergone an open procedure.…”
Section: Methodscontrasting
confidence: 81%
“…These urodynamic findings include an increase in the incidence of ISD, a decrease in cystometric capacity and bladder compliance, and an increase in both detrusor overactivity and detrusor under activity [5][6][7][8][9][10][11]. Some of these variables have been shown to improve with time, but even 3 years following prostatectomy, they may not parameters in patients who underwent radical retropubic (RRP) versus minimally invasive prostatectomy is not nearly as well reported.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…1 We agree with the authors that bladder strength has implications for the treatment of post-prostatectomy stress incontinence, because putting a compressive sling in a man with detrusor underactivity could lead to urinary retention. However, we question whether the criteria they used to identify detrusor underactivity is appropriate in men after radical prostatectomy.…”
mentioning
confidence: 45%